Missão das candidatas: a jornada jornalística da mulher na política brasileira - Rossa, Letícia Franciele (Universidade do Vale do Rio dos Sinos, 2024)
The Mission of the Candidates is the experimental guide that maps the journalistic journey of women in Brazilian politics. The anchor of the research is the exercise of power (in politics and journalism) as an effect of gender articulations: it’s through the attribution of certainties to women and men that hierarchical relationships are negotiated. In Brazil, politics is the institution that implements the extreme bottlenecks that place the masculine and feminine in the condition of antagonists; there are 52% Brazilian women in a country with 53% female voters, who elected 18% female candidates in 2022. There is a Brazil of women governed by men, in which President Dilma Rousseff appears as the greatest feminine mark to break rigid borders of a Brazil sewn with a masculine pronoun. The segregation of the largest portion of the population from the sphere of public policy does not occur in vain (Flávia BIROLI, 2018b), but as a nature of complex, deep-rooted and historical constructions that condition the male as the rule of existence and the female as a deviant position, on the other, as a non-man (Guacira Lopes LOURO, 1997). The example of the gendering of power is in ancestry and mythology, with the production of archetypes of the collective unconscious that reproduce the demands and limitations of gender – such as the Hero's Journey, from 1949 (CAMPBELL, 2007), and the Heroine's Journey, from 1991 (Maureen MURDOCK, 2022). Although these scripts appear as devices that open scenarios and provoke epistemological knowledge, there are insufficiencies in understanding what it means to be a hero or what it means to be a heroine. The Mission of the Candidates is a proposal to advance these journeys of theoretical-methodological analysis: through objective journalism (in investigation and ethics), but above all subjective (in affect and alterity), the provocation is to verify the fabrication of the narrative journalism (MOTTA, 2005a; RESENDE, 2009) as an agent that is also intertwined with gender impositions. News is a force that permeates social activity when it tells the life stories that permeate everyday life (Fabiana MORAES, 2022; Marcia VEIGA DA SILVA, 2010). The proposal of the thesis, then, is to present an analysis based on 24 news items from 168 copies and 13,486 pages from two Brazilian newspapers (Estadão and O Globo), using the Marcos de Dilma methodology (in which there is the systematization of a line of time with key dates in the former president's political history). As a result, the research identifies the arc of the Mission of the Candidates based on 12 stages of meaning that serve as a guide to understand how the journalistic narrative of women in Brazilian politics can be constructed. The proposal of the thesis is to sponsor concerns for subjective knowledge, but committed to accurate, dignified and horizontal information. It’s in the pages of this journalism that the production of fair knowledge that explores the dynamics of power for men and women is found. The Mission of the Candidates is a sample of a journalistic narrative that builds the journey of women in Brazilian politics. Although it does not present itself as a static and definitive form, the intention is to promote a reference that gives rise to reflections on the shape of journalism in situations that demand subjectivity in the telling of history. Therefore, this thesis is structured based on the duty to demand a journalistic narrative in which women's life stories in politics are not naturalized, conditioned or even made unfeasible.
Keywords: Gênero; Política; Narrativa jornalística; Dilma Rousseff; Jornada da heroína; Gender; Policy; Journalistic narratives; Heroine's journey; ACCNPQ::Ciências Sociais Aplicadas::Comunicação